Oceanographic patterns and carbonate chemistry in the vicinity of cold‐water coral reefs in the Gulf of Mexico: Implications for resilience in a changing ocean. (21st December 2015) - Georgian, Samuel E.; DeLeo, Danielle; Durkin, Alanna; Gomez, Carlos E.; Kurman, Melissa; Lunden, Jay J.; Cordes, Erik E.
Abstract: To accurately assess the threat that global climate change poses to marine systems, a detailed baseline of the current carbonate chemistry and other oceanographic conditions is required. Despite the heightened vulnerability of deep‐sea communities to ocean acidification, there have been relatively few studies investigating the carbonate chemistry immediately above cold‐water coral reefs. Here, we present data collected during five cruises from 2010 to 2014 in the northern Gulf of Mexico and quantify the carbonate system and other oceanographic parameters in offshore surface‐waters, the water column, and at deep benthic sites. Benthic sites containing the scleractinian cold‐water coral L. pertusa occurred in waters with a relatively wide temperature range (6.8–13.6°C), low potential density ( σθ = 26.9 ± 0.3 kg m −3 ), low dissolved oxygen concentration (111.3 ± 2.0 μmol kg −1 ), low pHT (7.87 ± 0.04), low ΩARAG (1.31 ± 0.14), and a low availability of carbonate ions (94.4 ± 9.2 μmol kg −1 ) compared with L. pertusa habitats in other regions. Based on previous modelling and experimental results, these values place L. pertusa at the edge of its viable niche in the deep Gulf of Mexico. However, significantly elevated total alkalinity (+39–44 μmol kg −1 ) was detected above large L. pertusa mounds, suggesting that carbonate dissolution within the mounds may be partially ameliorating the direct effects of ocean acidification. Together, these results provide an important baseline for assessing future oceanographic changes in the Gulf of Mexico and for predicting the resilience of cold‐water coral reefs to global climate and ocean change.